Absenteeism among undergraduate medical students and its impact on academic performance: A record-based study - Sayeli Mitra; Paramita Sarkar; Suchetana Bhattacharyya; Rivu Basu (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Student absenteeism is a major concern for undergraduate medical education training in India. Regular class attendance helps students have a proper understanding of the topic of discussion. This study explores the pattern of absenteeism among medical students and whether absenteeism is associated with their academic performances. MATERIALS AND METHODS: A record-based, cross-sectional study was done by reviewing departmental attendance registers, item cards and marks obtained in exam by 190 students in the community medicine department who had passed their 3rd professional part 1 examination in 2018. The data was entered and analyzed using SPSS version 16. A descriptive analysis summarizes the pattern of absenteeism and their marks obtained in the semester and professional exam of community medicine. The primary outcome indicator was the 3rd professional exam marks. The correlation between class absenteeism and other predictors and exam result was analyzed. Regression analysis was done to predict dependence of outcome variable on class attendance and formative examination marks. RESULTS: Overall, female students had better class attendance than male students. There was a positive correlation of lecture class attendance (r = 0.369) and marks obtained in the 6th semester exam (r = 0.717) with the final exam result. Further regression analysis showed final marks had a higher dependence on the 6th semester examination score (B = 0.669) when compared to lecture class attendance (B = 0.051). CONCLUSION: Although lecture class attendance is an important predictor of final result, this study showed that the 6th semester marks were a better predictor. This may be due to multiple factors (alternate source of learning, student's motivation, etc.) which require further exploration.